Performance and kinetic study of semi-dry thermophilic anaerobic digestion of organic fraction of municipal solid waste. (February 2015) - Sajeena Beevi, B.; Madhu, G.; Sahoo, Deepak Kumar
Highlights: Performance of the reactor was evaluated by the degradation of volatile solids. Biogas yield at the end of the digestion was 52.9 L/kg VS. Value of reaction rate constant, k, obtained was 0.0249 day −1 . During the digestion 66.7% of the volatile solid degradation was obtained. Abstract: Anaerobic digestion (AD) of the organic fraction of municipal solid waste (OFMSW) is promoted as an energy source and waste disposal. In this study semi dry anaerobic digestion of organic solid wastes was conducted for 45 days in a lab-scale batch experiment for total solid concentration of 100 g/L for investigating the start-up performances under thermophilic condition (50 °C). The performance of the reactor was evaluated by measuring the daily biogas production and calculating the degradation of total solids and the total volatile solids. The biogas yield at the end of the digestion was 52.9 L/kg VS (volatile solid) for the total solid (TS) concentration of 100 g/L. About 66.7% of the volatile solid degradation was obtained during the digestion. A first order model based on the availability of substrate as the limiting factor was used to perform the kinetic studies of batch anaerobic digestion system. The value of reaction rate constant, k, obtained was 0.0249 day −1 .